Bioassay-Guided Isolation and Identification of Bioactive Compounds from Garcinia Penangiana Leaves - Jabit, Mohd Lip (2005)
Preliminary screening was done on 18 extracts of different parts of Garcinia sp. These extracts were tested on cytotoxic assay by using MTT Tetrazolium method on MCF-7 cells (hormone dependent breast cancer cells), DU145 (prostate cancer cells), H460 (non-small lung cancer) and HL60 (Leukemic cancer cells). Extracts of G. penangiana leaves, Garcinia urophylla leaves, G. maingayi leaves, G-maingayi stems and G. opaca fruits were found to have potent cytotoxic activity on MCF-7 cells and their ICso values are 5, 3, 6, 10 and 8 pg/mL, respectively. Furthermore, the extract of G. penangiana leaves also showed potent cytotoxic activity towards H460 cells (ICSo value of 8 clg/mL ). Bioassay guided isolation and purification led to the isolation of five xanthones and triterpene compounds fiom Garcinia penangiana leaves extracts. The triterpene and sterol isolated were charaterized as friedelin (23) and stigmasterol (24), respectively. The two isolated xanthones fiom the hexane hction were characterized as 1,3,5,8- tetrahydroxy-4-(1 ,I -dimethyl ally1)xanthone (25) and cudratricusxanthone H (26). The two xanthones isolated from the dichloromethane extract were characterised as 1,3,5,6- tetrahydroxy-2-(1,l -dimethylallyl)-4-(3-methyl-2-buteny1)xanthone or macluraxanthone C (27) and the new penangianaxanthone (25). Compound designated as 29 was also found as a mixture of 27 in dichloromethane fraction. The biosynthesis of 25,26 and 28 was suggested in the discussion. These compounds were tested for cytotoxic assay by using MTT Tetrazolium method on MCF-7 cells (hormone dependent breast cancer cells), DU145 (prostate cancer cells) and H460 (non-small lung cancer cells). Compound 25,26, 27,28 and mixture of 29 and 27 exhibited good and potent cytotoxic activity on MCF-7, NCI-H460 and DU145 cell lines. However, 23 and 24 showed no activity toward MCF-7 and NCI-H460 cell lines. 26,27, 28 and mixture of 29 and 27 showed similar pattern of cytotoxic activity toward MCF-7 cell line with ICso values of 3.9 f. 0.8, 3.1 + 0.1, 5.8 + 1.2 and 3 -0 f. 0.2 pg/mL, respectively. Similar patterns of cytotoxic activity were also observed when 25, 26, 27, 28 and mixture of 29 and 27 tested on NCI-H460 cell lines. The compounds showed ICso values of 13.4 + 1.1 pg/mL, 5.0 f. 1.2 pg/mL, 1.4 + 0.9pg/mL, 4.5 f 1.4 and 2.0 f 0.7 pg/mL, respectively. 26,27,28 and mixture of 29 and 27 showed similar pattern of cytotoxic activity toward DU145 cell line with their ICso values of 4.6 f 0.2,2.6 + 0.6, 4.3 + 0.4 MmL and 3.0 f 0.4 pg/mL, respectively.